Análisis de las políticas públicas de salud y educación aplicadas por el Gobierno Autónomo Descentralizado Chone, período 2014-2019 - Arteaga Freile, Marlon Iván (2022)
The Decentralized Autonomous Governments enjoy certain functions granted by the Constitution and which are also described in the COOTAD, among these emphases is placed on the preparation and execution of public policies within the scope of their powers and in their territorial constituency. The purpose of this research is to analyze the public policies in the areas of health and education applied by the Autonomous Decentralized Municipal Government in Chone Canton, period 2014-2019, to determine their impact on the well-being of the population. In this way, study methods such as inductive, deductive and analytical-synthetic were applied, as well as the use of the interview as a research technique with which it was possible to publicize the public policies implemented in the study period and the projects with which answers were given to the problems evidenced in health and education issues, to later identify the scope that was obtained through them. The results that were obtained, as well as the conclusions that could be reached, show that the scope of the projects applied are of low percentages. Therefore, itisrecommended to carry out constant monitoring and evaluation of these policies or the projects that were launched, with the aim of identifying if the execution is being carried out adequately or, in turn, identifying shortcomings that cause delays in them.